Wolbachia strain w AlbB confers both fitness costs and benefit on Anopheles stephensi - Deepak Joshi; Michael J McFadden; David Bevins; Fengrui Zhang; Zhiyong Xi (Parasites & Vectors, 2014)
Abstract Background Wolbachia is a maternally transmitted intracellular bacterium that is estimated to infect up to 65% of insect species, but it is not naturally present in Anopheles malaria vectors. Wolbachia-based strategies for malaria vector control can be developed either through population replacement to reduce vectorial capacity or through population suppression to reduce the mosquito population. We have previously generated An. stephensi mosquitoes carrying a stable w AlbB Wolbachia infection and have demonstrated their ability to invade wild-type laboratory populations and confer resistance to Plasmodium on these populations. Methods We assessed w AlbB-associated fitness by comparing the female fecundity, immature development and survivorship, body size, male mating competiveness, and adult longevity of the infected An. stephensi to that of wild-type mosquitoes. Results We found that w AlbB reduced female fecundity and caused a minor decrease in male mating competiveness. We also observed that wAlbB increased the life span of both male and female mosquitoes when they were maintained solely on sugar meals; however, there was no impact on the life span of blood-fed females. In addition, w AlbB did not influence either immature development and survivorship or adult body sizes. Conclusions These results provide significant support for developing Wolbachia-based strategies for malaria vector control.